(untitled) (Aletria: Revista de Estudos de Literatura, 2009)
Resumo: O presente artigo tem por objetivo discutir a construção da herança narrativa advinda do texto homérico, pela Odisséia, enquanto partes constitutivas dos conceitos filosóficos de dom e temporalidade. Nesse sentido, buscou-se, pela análise da enunciação de Odisseu-narrador (entendida sempre como metáfora do próprio ato de narrar), compreender como o processo de nomeação produz um efeito de identidade na alteridade da recepção da herança clássica. Palavras-chave: Narração; dom; tempo. Abstract: This article aims to discuss the construction of the narrative heritage arising from the Homeric narrative, in the Odyssey, as constituent parts of the philosophical concepts of gift and temporality. Therefore, by the analysis of the enunciation of Odisseus-narrator (always understood as a metaphor to describe the act of narration itself), we understand how the nomination process produces an effect of identity on the alterity of classical heritage reception. Keywords: Narration; Gift; Time.